Impact of the Events of Saqifa on the Formation of Differences between the Islamic Sunni and Shia Tradition - Tahiiev, Akif (Journal of Al-Tamaddun, 2023)
There were a number of events in early Islamic history that caused controversy among the first generations of Muslims. In our opinion retrospective analysis of these events can reveal the prerequisites for the emergence of certain characteristics that have become specific to the main directions of Islam. This essay presents an analysis of one such event and its impact on the differences in the sources of Sunni and Shia Islamic traditions. During the events of Saqifa the successor to the Prophet was chosen, which played a significant role in the division of the Muslim community. We analyzed how these events influenced the understanding of divine law and the role of ijma and aql in Sunni and Shia doctrines.